Developing the Research Infrastructure in the Social Sciences: The Role and Contribution of the German Research Foundation - Eckard Kaemper; Manfred Niessen (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2008)
The DFG's (German Research Foundation) strategy for future data research infrastructures should be based on what has been achieved thus far and the lessons that can be learned: First, the focus should be on "providing data" rather than on "sharing data." Second, projects whose primary purpose is to provide a common good should seek to build research infrastructure. The DFG has powerful means at its disposal for funding outstanding infrastructure projects. It is up to the scientific community to adapt and utilize these funding instruments. Strategic cooperation is required among all the interested parties in the field: cooperation on thematic priorities within the research community; cooperation on options for funding between the research community and funding institutions; cooperation on the division of labour between the funding institutions (including ministries), both on the national and on the international level. The DFG is prepared to play an active role in this cooperation under the leadership of its elected bodies (Fachkollegien and Senat).
Keywords: 330; Large Scale Studies; Strategic Cooperation